Antibacterial effectiveness of different zinc salts on Streptococcus mutans and Streptococcus sobrinus: An in-vitro study - Manal Mohamed Almoudi; Alaa Sabah Hussein; Nurul Izzah Mohd Sarmin; Mohamed Ibrahim Abu Hassan (Saudi Dental Journal)
Objectives: This in-vitro study aimed to evaluate the antibacterial effects of four zinc salts namely zinc chloride, zinc sulfate, zinc citrate and zinc acetate against Streptococcus mutans (S. mutans) and Streptococcus sobrinus (S. sobrinus). Methods: Antibacterial susceptibility assay, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were undertaken to evaluate the inhibitory activities of different zinc salts against the tested bacteria. A scanning electron microscope (SEM) was used to evaluate the morphological changes of bacterial cells following exposure to zinc salts. Kruskal-Wallis and Mann-Whitney tests were used to compare the inhibitory effect of the different zinc salts. Results: All zinc salts tested against S. mutans and S. sobrinus had a statistically and significantly smaller inhibition zone when compared to chlorhexidine, (P < 0.001). However, zinc chloride had the largest inhibition zone (20 mm ± 5.5) against S. sobrinus, which was comparable to chlorhexidine (22 mm ± 4) (P > 0.05). Zinc chloride, zinc sulfate and zinc acetate demonstrated higher MIC and MBC values against S. mutans compared to S. sobrinus. However, zinc citrate revealed the highest MIC and MBC values of 1 mg/mL and > 8 mg/mL for S. sobrinus and > 8 mg/mL for S. mutans, respectively. Conclusion: Different zinc salts have displayed inhibitory growth effects against the common oral bacteria at very low concentrations except for zinc citrate which showed no inhibitory effect against these bacteria in vitro.